Salafisme di Papua, Indonesia: Sebuah Kajian Mengenai Kelompok Salafi-Wahhabi Ja'far Umar Thalib - Ridwan NA (ISLAM NUSANTARA:Journal for the Study of Islamic History and Culture, 2021)
The study of Salafism in Indonesia has been narrated its presence, development, activities and ideology in Java. In-depth research on Salafism in Papua is relatively inadequate. This article aims to fill the gap by studying Salafism, specifically the Salafy group of Jafar Umar Thalib (JUT) in Jayapura City and Keerom Regency, Papua. In addition, the responses of local community and Nahdhatul Ulama (NU) Papua toward JUT group will be reviewed. This article is based on the author's field research in Papua in 2018. The main data was collected from interviews, observations and publications related to Salafi-Wahhabi groups. Meanwhile, to explore the perceptions and responses of stakeholders, local communities and organisations, the authors interviewed informants from local residents and leaders of the Papua and Keerom NU Region. This article argues that the presence of Salafism tends to disrupt community harmony and peacebuilding in Papua. Such understanding provides a holistic view of how Salafism has sought to shape its narrative in Papua and NU Papua has rejected the narrative, which has received less attention from researchers in the past.